Forecasting the leverage listed companies in Tehran Stock Exchange with the help of simulating models - Mohammad Osoolian (تحقیقات مالی, 2017)
Reviewing trend and forecasting the debt ratio is one of the attractive topics for investors, managers, financial analysts and creditors. In this research, in order to forecasting debt ratio for listed companies in Tehran Stock Exchange, target leverage and speed of adjustment to the target leverage were used in four simulation models. first, The process and the stability of the capital structure were investigated on a seasonal period of 11 years from the first quarter of 1383 to the third quarter of 1393. The results indicate that, If the review period of stability regime is prolonge, sustainable regime will be less. Often, sustainable regime occured in debt ratios higher than 4.0. The results of the simulation indicate that Time-varying Target Ratios Models and Flexible Target Zone Models have best function in debt ratio simulation in real data.